Clinical effect of short-term spinal cord stimulation in the treatment of patients with primary brainstem hemorrhage-induced disorders of consciousness - Huang, Weilong; Chen, Qiang; Liu, Lin; Tang, Jianhong; Zhou, Hua; Tang, Zhiji; Jiang, Qing; Li, Tao; Liu, Jianwu; Wang, Dong (Frontiers in Neurology, 2023)
Objective Recently, short-term spinal cord stimulation (st-SCS) has been used in neurorehabilitation and consciousness recovery. However, little is known about its effects on primary brainstem hemorrhage (PBSH)-induced disorders of consciousness (DOC). In this study, we examined the therapeutic effects of st-SCS in patients with PBSH-induced DOC. Methods Fourteen patients received a 2-week st-SCS therapy. Each patient's state of consciousness was evaluated using the Coma Recovery Scale-Revised (CRS-R). CRS-R evaluation scores were recorded at the baseline (before SCS implantation) and 14 days later. Results Over 70% (10/14) of the patients (CRS-R score increased to ≥2 points) responded to the SCS stimulation after 14 days of st-SCS treatment. All items included in the CRS-R exhibited a significant increase post-treatment compared with pretreatment. After 2 weeks of st-SCS treatment, seven patients showed diagnostic improvement, resulting in a 50% (7/14) overall effective rate. Approximately 75% (3/4) of patients with minimally conscious state plus (MCS+) improved to emergence from MCS (eMCS), and 50% (1/2) of patients with vegetative state or unresponsive wakefulness syndrome (VS/UWS) improved to MCS+. Conclusion In PBSH-induced DOC, st-SCS is a safe and effective treatment. The clinical behavior of the patients improved significantly following the st-SCS intervention, and their CRS-R scores markedly increased. This was most effective for MCS+.